Nano-scale analysis of moisture diffusion in asphalt-aggregate interface using molecular simulations. (24th May 2021) - Zhou, Xinxing; Moghaddam, Taher Baghaee; Chen, Meizhu; Wu, Shaopeng; Adhikari, Sanjeev; Wang, Fusong; Fan, Zepeng
Graphical abstract: Highlights: Nano-scale moisture migration model in the asphalt-aggregate interface is built for the first time. The nano-scale moisture distribution in asphalt-aggregate interface was investigated. Effects of aggregate type, humidity and hydraulic pressure on moisture diffusion in asphalt-aggregate interface are studied. Abstract: Presence of moisture can weaken the asphalt-aggregate bond and result in aggregate stripping and moisture damage in asphalt mixture. This study investigates how the moisture affects the asphalt-aggregate bond and simulates moisture distribution of nano-scale in asphalt-aggregate interface. Effects of aggregate type (basalt, dolomite and limestone minerals), humidity and hydraulic pressure on moisture diffusion in asphalt-aggregate interface are studied. Diffusion coefficient (D), radial distribution function (RDF), contact angle (CA), free volume (FV) are calculated through molecular dynamic simulations. Polarizability of moisture in the asphalt-aggregate interface was measured using density function theory (DFT). Nano-scale moisture migration model in the asphalt-aggregate interface is built for the first time. The results show that D depends more on the hydraulic pressure than humidity and aggregate type which represents the significance of hydraulic pressure on the moisture diffusion. In addition, the aggregate type has significant effects on RDF, CA and FV. DFT results indicate that polarizability of moisture changes for different types of aggregate and hydraulic pressure values. In the asphalt-water-aggregate interface, the asphalt competitively interacts with moisture and ions from minerals through intermolecular forces.